Criminal Liability for People of Physical Abuse by Children - Risdianto, Muhammad Faisal (Universitas Muhammadiyah Tangerang, 2024)
This research is driven by the growing issue of physical bullying, where diversion efforts have proven ineffective in deterring perpetrators. The study aims to examine and analyze the legal protection provided to child victims of physical bullying and the criminal liability of child perpetrators. This research employs a normative juridical method, utilizing both statutory and conceptual approaches. The findings reveal that legal protection must be afforded to children who fall victim to criminal acts, including physical bullying. In offering such protection, it is essential to uphold principles of non-discrimination, the best interests of the child, the child’s right to survival and development, and respect for the child’s views. Furthermore, child victims of physical abuse may seek restitution from the perpetrator. The author argues that imprisonment can serve as an effective deterrent for child perpetrators, as they meet the criteria for criminal responsibility. However, diversion is more suitable for minor offenses or crimes involving damage to property.Keywords: Criminal Liability, Physical Abuse, Children